OPTIMALISASI TEKNOLOGI SPAM UNTUK MENDUKUNG PELAYANAN AIR BERSIH DI KAWASAN STRATEGIS BANDARA INTERNASIONAL JAWA BARAT - HERYADIANA, ASEP DIAN; Rachmat, Agus; Kadir, Yushar (J-ENSITEC, 2024)
The increasing demand for clean water services in Majalengka Regency, especially in the strategic area of West Java International Airport (BIJB), necessitates optimal performance from PDAM Majalengka. This study aims to evaluate and optimize SPAM technology implementation to enhance water distribution services. Using quantitative analysis through surveys and statistical testing with SPSS, findings indicate that key factors such as water pressure, continuity, quality, pricing, and complaint handling significantly influence customer satisfaction. Recommendations include upgrading distribution networks, optimizing existing water sources, and adopting advanced SPAM technologies to meet future demands.